Cover Image, Volume 13, Issue 3. (2nd May 2019) - Jeon, Jong Yeol; Han, Yohan; Kim, Young‐Wun; Lee, Youn‐Woo; Hong, Sukwon; Hwang, In Taek
Abstract : The cover image is based on the Review Feasibility of unsaturated fatty acid feedstocks as green alternatives in bio‐oil refinery by Jong Yeol Jeon et al., DOI:10.1002/bbb.1979 . Designed by Kyung Ha Hwang. Abstract : The cover image is based on the Review Feasibility of unsaturated fatty acid feedstocks as green alternatives in bio‐oil refinery by Jong Yeol Jeon et al., DOI:10.1002/bbb.1979 . Designed by Kyung Ha Hwang.